Sinchronic Colorectal Tumors - Baldizán, Jorge; Estefan, Alberto; Gateño, Nisso; Rompani, Omar; Navarro, Teodoro (Cirugía del Uruguay, 1981)
The incidence of sinchronic colorectal lesions amongst patients with tumors of the colon is statistically of 4,5 o/o.